Implementation and evaluation of control strategies based on an open controller for a 10 MW floating wind turbine. (December 2021) - Hu, Ruiqi; Le, Conghuan; Gao, Zhen; Ding, Hongyan; Zhang, Puyang
Abstract: The reliability assessment concerning the drivetrain system is important for integrated dynamic analysis of large-scale floating wind turbines (FWTs). An open, modular, and adaptable baseline wind turbine controller is implemented and evaluated in this paper to work with the DTU 10 MW reference wind turbines supported by a proposed Tension Leg Platform (TLP). Higher natural frequency of the controller can account for the coupling effects between the blade pitch control and the platform motions that contributing to poor performances of the FWT and negative damped pitch motions. Through simulations by FAST code, the baseline controller is evaluated by comparing the conventional pitch-to-feather strategy and the active pitch-to-stall strategy. The controller is detuned with different control frequencies and the active stall control strategy is tailored for the proposed TLPFWT. The results suggest that system instabilities induced by higher control frequency decreases fast as the growth of wind speed and the stall controller can lead to around twice platform motions and structure force as large as baseline controller in a wide range of frequency, whereas the rotor performance is fine. The DRC working with FAST proves applicable and different control algorithms and the integrated dynamic effects with other floating foundations can be achieved.